Optimasi Formula Emulgel Serbuk Kasar Papain - MOCH FUTUCHUL ARIFIN; SYARMALINA SYARMALINA; DIANA SYARMALINA; SHAFA NABILAH; DIDA MAULIDA HASANAH; HIFZIEL AZHAR (Fakultas Farmasi Universitas Pancasila, 2015)
Crude powder of papain is very irritative and unstable, thus it should be formulated in emulgel using factorial design 2. The purpose of the study was to assess the effect of gelling agent (2.5% HPMC, 1 % Carbomer 940 ), oil phase ( liquid paraffin 5% to 7.5 % ), emulsifier ( 1.5% -2% Tween 80 - Span 80) and determine the optimum formula. Viscosity, ease of spread, proteolytic activity and antimicrobial activity of papain emulgel were used as the parameters in formula optimization. Each parameter had a contour plot. With the use of superimposed countor plot, the shaded area could be determined as the optimum formula. The results of the factor effect analysis and its interactions were that gelling agent gave significant effect (p<0.05) and dominant in increasing the viscosity of emulgel and the activity of papain proteolytic enzyme. However, it decreased the diameter of the dispersing area and the inhibition zone diameter. The increase in the concentration liquid paraffin concentration had a dominant and significant effect towards the improvement of the emulgel’s dispersive power and the proteolytic activity of papain. The increase in the combination of Tween 80-Span 80 emulgator had a dominant and significant effect towards the improvement of viscosity and the decrease in the dispersive power, the proteolytic activity, and the inhibition zone diameter. From the superimposed contour plots analysis and response optimizer, the optimum formula was achieved by 2.5% of HMPC gelling agent, 5.6% of liquid paraffin, and 2.4% of emulsifier combination.